Musicians Of Salamander Big Band Bandung (A Study On Motivation, Competence, And Creativity) - Buntoro, Bonny (Journal of International Scholars Conference - EDUCATION/SOCIAL SCIENCES, 2016)
This paper aims to investigate motivation, creativity and competence among the musicians of Salamander Big Band, Bandung. The study gives some theoretical contributions, such as 1) broadening horizons in managing human resources that can be used as a reference for the study of human resource development in the future, 2) expanding the study of science management that related to the field of music, and 3) adding a new concept that can be used as material references for further research for the development of music management. The study which was conducted in Salamander Big Band Jl. Kiputih 12 Balai Pertemuan Sangkuriang Bandung used qualitative method. The data from the musicians are collected and analyzed to gain an understanding of social phenomena-culture about motivation, creativity, and competence in musicians. The results of this study showed that motivation, creativity and competence of the musicians in Salamander Big Band is quite good although not optimal. Thus, more effort is required to improve more in the future. Keywords: Motivation, Competence, Creativity, Musicians, Big Band.